Análise do processo de comercialização pelo programa de aquisição de alimentos, por meio do Termo de Adesão municipal - 2015 e 2016: o caso dos restaurantes populares de Belo Horizonte - MG - Gomes, Edina Neves Teixeira Fialho (2017)
The present study had the objective of understanding some of the social relations between farmers and governmental actors in the commercialization process of products derived from family agriculture by the Food Acquisition Program (FAP), using the purchase mode with simultaneous donation, by means of the municipal Adhesion Term, for supplying popular restaurants in Belo Horizonte, in Minas Gerais, Brazil. The research combined qualitative and quantitative approaches, with the application of 90 questionnaires with family agriculture farmers of 18 municipalities, which trade the production to popular restaurants in Belo Horizonte, and performing interviews guided by semi-structured scripts with three managers of the Municipal Secretariat Deputy to the Nutritional and Food Safety (MSDNFS) and one local extensionist from Emater -MG. For the data analysis, we considered the results from both moments: the quantitative data received statistical treatment, and the qualitative information were worked using co ntent analysis. The last were evaluated from the perspective of collecting data for building the subject profiles and identifying the contribution of FAP for strengthening and increasing the income of family farmers, and the mechanisms used by the family farmers for access and delivery of the production to the popular restaurants; the perception of the managers of MSDNFS and the perception and role of the extensionists from Emater-MG, on the execution of the FAP. The data surveyed from the family farmers showed that the commercialization of their products to popular restaurants contributes for establishing relations with other farmers, with extensionists from Emater -MG, with the local public power, with organizations and even with other markets. The managers of MSDNFS and local extensionists from Emater-MG showed the importance of this FAP mode to family farmers, for allowing the strengthening of family agriculture while improving food quality for the consumer beneficiaries of the popular restaurants. In addition to the acquisition of products from family farmers, the program contributes for improving the knowledge on the production and on other markets, ant the strengthening of the established social relations.